Promotion-Linked Training Program in Punjab: Analysing Educational Managers’ Satisfaction through Demographic Lenses - Zil e Huma; Muhammad Nadeem Anwar (`, 2025)
It is widely acknowledged that enhancing the caliber of education managers is crucial to upsurge the standard of education. This entails launching wide-ranging training programs intended to equip them for the challenges of their roles, along-with a robust evaluation to gauge training effectiveness. The study aimed to provide a demographic analysis of educational managers’ level satisfaction as part of a broader evaluation of the Promotion-Linked Training program’s effectiveness using Kirkpatrick's four-level model. However, though this paper specifically focuses on the evaluation of educational managers’ level of satisfaction with the Promotion-Linked Training program through the lens of demography factors including gender, qualification, and experience. Therefore, demographic factors of 264 educational managers were analyzed using inferential statistics. It was revealed that gender, academic qualification, and years of administrative experience have no statistically significant influence on the satisfaction levels of educational managers. Thus, the findings confirms that the PLT program is effective across demographics. Its effectiveness is not confined to a particular gender, qualification level, or experience bracket, suggesting it is a fundamentally sound and well-conceived initiative. Keywords: Promotion linked training, educational managers, satisfaction, demographic analysis